'n Ondersoek na die konjunktuurverskynsel met besondere verwysing na die fases van die konjunktuurgolf (2014)
M.Com. === In this treatise, research is done into the various theories with regard to the business phenomenon and the various phases of the business cycle according to various economic indicators. A characteristic of the South African economy as well as other capitalistic systems, is that business indicators have a unstable tendency. Times of prosperity are followed by times of recession when unemployment, production, prices, profits and economic welfare, decline. The recession is again followed by times of prosperity which are characterised by increases in job opportunities as well as rising prices, profits and living standards. This wave like movement in economic activity is known as the business phenomenon. There are certain forces which directly affect the business cycle - some of them force it upwards while others force it downwards. The direction of the business cycle depends on the dominant forces. As soon as the forces are exhausted, a turn in the cycle results. The series regarding the business cycle are classified according to specific schools of thought in order to investigate their development as well as the main causes of the wave like motion in economic activities. A simple classification can be made by dividing the theories into those which preceded the publication of J.M. Keynes' General Theory of Employment, Interest and Money in 1936 as the Classical or Pre-Keynesian, and those which form the Keynesian school of thought and which appeared since the thirties as the Post-Keynesian theories. Firstly the Pre-Keynesian business cycle theories are discussed with reference to amongst others the demand theories, supply theories, the monetary theories and. the impulse theories. Thereafter the Post-Keynesian business cycle theories are discussed, that is those of Hicks, Kalecki, Goodwin and Duesenberry. An examination of the different phases of the business cycle implies a study of the movement of economic data in a upward and downward direction. Four phases can be discerned within the business cycle namely: the upward phase, the upper turning point, the downward phase and the lower turning point. The position of the various indicators will determine in which phase a country's economy finds itself. Economic activities are never stagnant, with the result that a period of prosperity may be followed panicking or a pez'Lod of depression. Several economic indicators may indicate this sequence, for instance unemployment, declining output and profit margins, and the resulting loss of income on the national level. As soon as the lower turning point is reached, the economy starts to recover and a period of prosperity again follows. It can thus be argued that the business cycle is a result of interaction between demand and supply. The business cycle has a significant result on the economy as a whole. It influences the prosperity of the country and even that of the undertaking, its manpower position, its capacity occupation and its factors of production. Every individual is effected to the extend that his disposable income is directly determined by the position of the business cycle. The phases of the business cycle and the inclining and declining motion of economic data contains the nucleus of the effect of the external environment on the undertaking.